2018
DOI: 10.1038/s41598-018-31556-6
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of the low-oxygen-activated locus of Burkholderia cenocepacia in adaptation during cystic fibrosis infection

Abstract: Chronic infection with opportunistic pathogens including Burkholderia cepacia complex (Bcc) is a hallmark of cystic fibrosis (CF). We investigated the adaptive mechanisms facilitating chronic lung infection in sequential Bcc isolates from two siblings with CF (P1 and P2), one of whom also experienced intermittent blood-stream infections (P2). We previously showed increased lung cell attachment with colonisation time in both P1 and P2. WGS analysis confirmed that the isolates are closely related. Twelve genes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…These late chronic infection isolates also showed increased attachment to CF lung epithelial cells [12]. Importantly, all six USPs encoded on the lxa locus showed increased abundance with time of colonisation [11]. Among these lxaencoded usp genes, BCAM0276, encodes a UspA family stress protein which consistently showed increased abundance in the later isolates from two chronically colonised patients and was associated with increased gene expression [11].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…These late chronic infection isolates also showed increased attachment to CF lung epithelial cells [12]. Importantly, all six USPs encoded on the lxa locus showed increased abundance with time of colonisation [11]. Among these lxaencoded usp genes, BCAM0276, encodes a UspA family stress protein which consistently showed increased abundance in the later isolates from two chronically colonised patients and was associated with increased gene expression [11].…”
Section: Introductionmentioning
confidence: 95%
“…Having characterised USP76, we wanted to examine whether other USPs expressed within the locus share the same functions. We chose a uspA gene downstream of BCAM0276 as it was upregulated by 201-fold in response to low oxygen and showed greatest increase in protein abundance (up to 16 fold) in late stage isolates [10,11]. A targeted single deletion mutant was generated for the BCAM0292 gene; however, despite many attempts we were unable to complement the strain with the BCAM0292 gene.…”
Section: The Usps Encoded In the Lxa Locus Are Not Redundantmentioning
confidence: 99%
See 2 more Smart Citations
“…Viability loss is also observed in oxygen-free environments, indicating the importance of the gene in B. cenocepacia during oxygen depletion. A study conducted by Cullen and co-workers found that among the 19 proteins that play a potential role in electron transfer, metabolism and regulation encoded by the lxa gene elevated during chronic infection, six are USPs and a heat shock protein [ 57 ]. All the proteins exhibited an increase (of up to 40-fold) in production during chronic lung infection.…”
Section: Usps In Cystic Fibrosismentioning
confidence: 99%